2011
DOI: 10.1111/j.1365-2591.2010.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of several fibre‐reinforced composite restoration techniques on cusp movement and fracture strength of molar teeth

Abstract: Regardless of restoration technique, fibre reinforcement of composite restorations decreased cusp movement in molar teeth with MOD and endodontic access cavities but did not affect fracture strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 42 publications
3
46
2
3
Order By: Relevance
“…In addition, it has been reported that placing a Ribbond on the occlusal surface could increase the fracture resistance of premolars with MOD cavity 13) . Another study demonstrated that anterior teeth restored with a Ribbond inside a root canal achieve a higher resistance strength to fracture 16) . It is thought that combined FRC and dentin as a whole, therefore, if a load force is applied to the sample, the fiber would absorb it and reduce the risk of fracture as the intact tooth 12,16) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it has been reported that placing a Ribbond on the occlusal surface could increase the fracture resistance of premolars with MOD cavity 13) . Another study demonstrated that anterior teeth restored with a Ribbond inside a root canal achieve a higher resistance strength to fracture 16) . It is thought that combined FRC and dentin as a whole, therefore, if a load force is applied to the sample, the fiber would absorb it and reduce the risk of fracture as the intact tooth 12,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that anterior teeth restored with a Ribbond inside a root canal achieve a higher resistance strength to fracture 16) . It is thought that combined FRC and dentin as a whole, therefore, if a load force is applied to the sample, the fiber would absorb it and reduce the risk of fracture as the intact tooth 12,16) . During normal function, the cusps of the opposing tooth exert a wedding effect that pushes the B and L cusps apart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep endodontic access preparation in the MOD cavity has been found to increase cuspal deflection significantly [50]. Akman et al (2011) [72] reported that fiber-reinforced composite restorations decrease cusp movement in molar teeth with MOD and endodontic access cavities. As a result, fiber reinforcement of composite resin restorations with polyethylene or glass fiber material is a well-accepted method for saving the remaining tooth structure while performing direct composite restorations in root-filled teeth.…”
Section: Fiber-reinforced Composite Materialsmentioning
confidence: 99%